CHARACTERIZING AND QUANTIFYING SOLID WASTE IN VITIS RURAL COMMUNITY, LIMA, PERU - Jaime-Huaman, Emerson (2021)
Solid waste was characterized and quantified in a rural community, district of Vitis, in the province of Lima, Peru in order to determine the district's per capita production, density, composition and humidity of household and non-household waste for proper planning of the management. In the first category, a per capita generation of 0.39 kg/hab/day, density 241.61 kg / m, composition UW (usable waste) (77%), UUW (unusable waste) (23%), OW (organic waste) (69%), RI (inorganic waste) (8 %) and plastic (1.86%) of the total collected, followed by glass, paper, cardboard, textiles, packaging, rubbers and metals), with humidity (72.10%). And in the second category there was a per capita generation of 0.29 kg/hab/day, density 213.62 kg/m, composition UW (66%), UUW (34%), OW (44%), IW (22%) and plastic (4.5%) of the total collected, followed by glass, paper, cardboard, packaging, textiles and metals, with humidity (69.29%).